Atherosclerosis fate in the era of tailored functional foods: Evidence-based guidelines elicited from structure- and ligand-based approaches. (October 2022) - Azevedo, Luciana; Serafim, Mateus Sá M.; Maltarollo, Vinícius G.; Grabrucker, Andreas M.; Granato, Daniel
Abstract: Background: Atherosclerosis is the primary cause of cardiovascular diseases (CVDs), contributing to more than 33% of the annual deaths globally. Westernized dietary patterns, a high prevalence (50%) of overweight and obesity, and an increased incidence of glucose intolerance and type-2 diabetes are related to atherosclerosis. However, increased demand for functional foods has boosted the production of different foods to improve people's life quality and decrease the CVDs' risk. Nonetheless, functional foods targeting CVDs are scarce in the marketplace. Scope and approach: To perform a multidisciplinary and cross-sectoral approach by linking atherosclerosis biomarkers, potential bioactive compounds (e.g., phenolics), and food technology, besides scientific limitations, we propose a practical step-by-step guide to designing functional foods. First, a comprehensive and up-to-date overview of atherosclerosis is provided, focusing on the inflammation markers to counteract its onset and progression. Then, a structure-based–(SBDD) or ligand-based drug design (LBDD) approach is presented, and illustrated by the incorporation of vescalagin, a phenolic compound from jaboticaba seed, into a functional food to mitigate atherosclerosis. Key findings and conclusions: Tailored functional foods added with phenolic compounds can be designed through computational approaches predicting their bioactivity. Together with chemical analyses, mathematical models can explore a vast array of molecular mechanisms, allowing the discovery of novel bioactive compound sources. Altogether, food science/technology, nutrition, and structure- and ligand-based approaches should be combined to support the design of tailor-made functional foods/nutraceuticals to contribute to public health interventions related to atherosclerosis and other cardiometabolic diseases. Graphical abstract: Image 1 Highlights: Cardiovascular diseases (CVDs) are the main cause of death but can be prevented. Consumers look for functional foods to decrease the risk of CVDs but few are available. Food/Pharma companies should consider developing new foods and nutraceuticals. Food science, CVD therapy and in silico modelling should be linked to produce functional foods to mitigate atherosclerosis.